Major HIV vaccine candidates - Zdziennicki, Wojciech; Zimnicki, Patryk; Lato, Marta; Iberszer, Konrad; Litwiniuk, Maria; Zaniuk, Marcin; Hurkała, Kamil; Antonik, Dominika; Denys, Barbara; Góra, Karolina (Journal of Education, Health and Sport, 2023)
Introduction and objective: Human immunodeficiency virus (HIV) is a virus, which is responsible for an acquired immunodeficiency syndrome (AIDS). This pathogen is widespread worldwide causing a pandemic that has been going on for decades. Researches around the world are trying to end this situation and it seems that the greatest hope lies in finding an effective vaccine. It is important due to the fact that AIDS and its consequences are responsible even nowadays for death of many people infected around the world. The aim of this study was to provide the most important information about major HIV vaccine trials and efficacy of vaccine candidates. Materials and methods: For the purposes of writing this article, the available literature was reviewed. The database of medical publications – Pubmed datebase and other publicaly available books, database and online sites was searched, with the use of keywords such as HIV, HIV vaccine, HIV epidemiology. State of knowledge: According to review studies HIV vaccine trials has been going for 4 decades. Over 250 trials has been conducted since then, but unfortunately, none of them resulted in effective vaccine. The difficulties of this task are mainly connected with the nature of HIV virus. To date, one study has shown some effectiveness, but not enough to claim success. Other studies are ongoing around the world and more are planned. Conclusions: Developing an effective HIV vaccine is the clue to solving the problem, which is new HIV infections. Further researches, further research funding and international cooperation are needed to end this pandemic.